2016
DOI: 10.1016/j.jiph.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus infection among children hospitalized for febrile illness suspected to be dengue in Barbados

Abstract: Emerging picture of hantavirus infection in the South America is characterized by greater proportion of childhood infection and wider spectrum of disease from mild asymptomatic to lethal cardiopulmonary disease. Barbados is endemic for dengue and leptospirosis, both of which share clinical features with hantavirus infection and in many cases neither of these diagnosis could be confirmed. We investigate whether some of the children hospitalized with suspected dengue could indeed have been hantavirus infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(62 reference statements)
1
7
0
1
Order By: Relevance
“…Hantavirus transmission in Barbados has been detected since 2001 among febrile persons under investigation for acute DENV infection and in wild rats [25,26]. Hantavirus infections have remained endemic in Barbados since then however the identity of the circulating strain(s) has proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Hantavirus transmission in Barbados has been detected since 2001 among febrile persons under investigation for acute DENV infection and in wild rats [25,26]. Hantavirus infections have remained endemic in Barbados since then however the identity of the circulating strain(s) has proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Hantavirus are emerging viruses transmitted by inhalation of rodent secretions, and responsible for Hantavirus Pulmonary Syndrome in Latin America [42]. Patients with confirmed acute hantavirus infection are mistakenly assumed to have DENV infection or leptospirosis, due to their similar clinical features and the endemicity of the latter two diseases in the region [24]. Epidemiological studies have shown noticeable differences in seroprevalence of antibodies against hantaviruses in humans ranging from 1% to 13.5%, according to geographical and ethnic differences [43,44].…”
Section: Hantavirusmentioning
confidence: 99%
“…Exposure to rural areas and history of peridomestic activities are some of the risk factors most reported [45]. Studies investigating recent hantavirus infection in febrile patients found a prevalence that ranges from 0.3% to 14% [10,24,44,46].…”
Section: Hantavirusmentioning
confidence: 99%
“…Por lo tanto, es aconsejable utilizar una aproximación síndromatica, en la cual la evaluación de la presencia de una infección por hantavirus se hace al mismo tiempo, de la causada por otros agentes que causan cuadros clínicos similares. Los hantavirus han sido asociados a 3 síndromes infecciosos: a) el síndrome febril de origen viral con síntomas respiratorios; b) el síndrome pulmonar: c) el síndrome febril hemorrágico con compromiso renal (32). (30).…”
Section: Epidemiología De Los Hantavirus En Lasunclassified